Nitric Oxide Modulates the Activity of Tobacco Aconitase - Navarre, Duroy A. (American Society of Plant Physiologists, 2000)
Recent evidence suggests an important role for nitric oxide (NO) signaling in plant-pathogen interactions. Additional elucidation of the role of NO in plants will require identification of NO targets. Since aconitases are major NO targets in animals, we examined the effect of NO on tobacco (Nicotiana tabacum) aconitase. The tobacco aconitases, like their animal counterparts, were inhibited by NO donors. The cytosolic aconitase in animals, in addition to being a key redox and NO sensor, is converted by NO into an mRNA binding protein (IRP, or iron-regulatory protein) that regulates iron homeostasis. A tobacco cytosolic aconitase gene (NtACO1) whose deduced amino acid sequence shared 61% identity and 76% similarity with the human IRP-1 was cloned. Furthermore, residues involved in mRNA binding by IRP-1 were conserved in NtACO1. These results reveal additional similarities between the NO signaling mechanisms used by plants and animals.